Theory of Planned Behavior sebagai Upaya Peningkatan Kepatuhan pada Klien Diabetes Melitus - Ni Nyoman wahyu Lestarina (Media Kesehatan Masyarakat Indonesia, 2018)
Diabetes mellitus (DM) is a disease that often caused complications that require care and long-termtreatment. Preliminary study obtained from 10 respondents, 50% of clients difficult to comply with diet , 60% felttired and bored to the treatment of diabetes, 10% of clients have regular exercise , and 50% of clients said thatfear of complications of DM. The purpose of this study is developing model improved compliance based Theoryof Planned Behavior in client type 2 Diabetes Mellitus on Community Health Centre Gundih Surabaya. Thisstudy used explanative observational with cross sectional approach. The population in this research is type 2DM client who lives in community health centre Gundih Surabaya. Sampling technique used purposive samplingand 100 patient obtained as a sample. The variables in this study were age, sex, education, knowledge, attitudes,subjective norms, perceptions of control, intention, compliance management of diabetes and blood sugar levels.Data collection was using questionnaire and analyzed using PLS (Partial Least Square). Statistic analysis resultshows there is significant relationship between attitude, subjective norm and percieved behavioral control towardintention with t-value 13,935. There is significant relationship between intention with compliance with t-value7,80.There is significant relationship between compliance and blood sugar level with t-value 4,592. Theory ofPlanned Behavior (TPB) stated that behavior could effectd by intention, attitude, subjctive norm and percievedbehavioral control.